Relative skeletal maturity status affects injury burden in U14 elite academy football players - Monasterio, X.; Bidaurrazaga-Letona, I.; Larruskain, J.; Lekue, J. A.; Diaz-Beitia, G.; Santisteban, J. M.; Gil, S. M. (Scandinavian Journal of Medicine & Science in Sports, 2022)
Maturation progresses at different times and at different rates between individuals. Thus, differences in maturity status exist among players in the same chronological age-based category, especially in U14 players. The purpose of this prospective study was to describe injury burden according to the relative skeletal maturity status in U14 elite academy football players. From 2011 to 2020, injuries and individual exposure (training and match) were prospectively recorded in 183 male U14 players. Skeletal age (SA) was assessed using the Tanner-Whitehouse 2 method. Relative skeletal maturity status [SA minus chronological age (CA)] was classified as follows: early (SA-CA > 0.5), on-time (SA-CA ± 0.5), and late (SA-CA < -0.5). Overall and specific injury burden (days lost/1000 h) and rate ratios for comparisons between groups were calculated. Overall injury burden was 2.8 times higher (3.6 times in training) in early maturers compared with late maturers. Growth-related injuries were the most burdensome injuries in all three groups, but significant differences were not found between groups. Muscle injuries were 4 times more burdensome in early maturers compared with on-time and late maturers. Besides, joint/ligament injuries were 7 and 12 times less burdensome in late maturers than in on-time and late maturers, respectively. Significant differences between groups in overall and specific injury burden were not found in matches. Our results showed different injury patterns in U14 early, on-time, and late maturers. Hence, monitoring maturity seems crucial to detect potential injuries that cause the greatest disruption, and facilitate design of targeted injury prevention programs.